Kebijakan Pemerintah dalam Pemerataan Pembangunan Infrastruktur Jalan di Kota Palembang - Dilla Mardianty; Sunarto Sunarto; Mega Nugraha (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Dila Mardianty, Government Policy in Equitable Road Infrastructure Development in Palembang City. This study aims to describe and analyze Government Policy in Equitable Road Infrastructure Development in Palembang City. The research method used is qualitative with three methods of data collection, observation, interviews and documentation. The results of the study indicate that the Government’s Policy in Equitable Road Infrastructure Development in Palembang City has not been implemented optimally, this is due to the lack of human resources, supporting facilities and budgets, as well as support from the land community and participating in maintaining roads that have been built or are in the development process. Supporting factors, namely the existence of good cooperation in the bureaucratic structure at the Public Works Service and also the support of related parties and the inhibiting factors, namely the lack of facilities, budget and number of human resources, as well as community support.